2021
DOI: 10.3390/su13073653
|View full text |Cite
|
Sign up to set email alerts
|

Executive Gender and Firm Environmental Management: Evidence from CFO Transitions

Abstract: We investigate whether female executives influence corporate environmental management (green management). Based on a difference-in-difference approach, our study provides evidence that female CFOs conduct more environmentally responsible activities, and the effects are more prominent when firms are of high risks. Female CFOs are more likely to involve in environmental management voluntarily. Further, environmental management improves firm performance such as debt cost saving. This research advances the gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 76 publications
2
13
0
Order By: Relevance
“…In correspondence to the critical mass of women leader's H1, I created a dummy variable which I called "WO_TMT", and coded as one if at least three women prevail in the TMT, and zero otherwise. As many authors argued (Wang et al, 2021;Lim and Chung, 2021;Pan et al, 2020;Yang et al, 2019), this dummy variable allows the use of a single regression equation to represent multiple groups (female leaders [2] minority).…”
Section: Samplementioning
confidence: 99%
See 2 more Smart Citations
“…In correspondence to the critical mass of women leader's H1, I created a dummy variable which I called "WO_TMT", and coded as one if at least three women prevail in the TMT, and zero otherwise. As many authors argued (Wang et al, 2021;Lim and Chung, 2021;Pan et al, 2020;Yang et al, 2019), this dummy variable allows the use of a single regression equation to represent multiple groups (female leaders [2] minority).…”
Section: Samplementioning
confidence: 99%
“…Second, Furlotti et al (2019) found that, consistent with gender self-schema, women pay more attention to social initiatives when they are in the chairperson's position. Two recent seminal empirical analyses by Lim and Chung (2021) and Wang et al (2021) revealed that companies led by female CEOs participated in more socially and environmentally responsible activities overall.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this cluster depicts the significance of environmental disclosures and performance considering the role of TMT characteristics. First, several studies documented that female CFOs, directors, and CEOs significantly enhance environmental performance (Elmagrhi et al 2019;Tran and Pham 2020;Wang et al 2021). Second, studies in the cluster found mixed evidence regarding the relationship between TMT education and environmental performance.…”
Section: Thematic Mapmentioning
confidence: 99%
“…Female CFOs also improve firm performance such as debt cost saving as they conduct more environmentally responsible activities, whose effects are more prominent in high risk firms (Wang et al, 2021).…”
Section: Sustainability Effects On Firm Performance and Valuementioning
confidence: 99%